The Effect of an 8-week NASM Corrective Exercise Program on Upper Crossed Syndrome - Mahsa Abdolahzad; Hassan Daneshmandi (Islamic Azad University, Hamedan Branch, 2019)
Objective: Upper Crossed Syndrome (UCS) is a disorder caused by muscle imbalance of the upper quadrant of the body. Using National Academy of Sports Medicine (NASM) protocol for corrective exercises is one of the new approaches to restore muscle balance, and prevent/correct postural abnormalities. The purpose of the present study is to evaluate the effect of an 8-week NASM corrective exercise program on UCS. Methods: Participants were 30 female students with forward head > 46 degrees, forward shoulder > 52 degree and thoracic kyphosis > 42 degrees, who were selected using a purposive sampling method and then randomly divided into control and intervention groups. The intervention group received corrective exercise program for eight weeks, three sessions per week. Forward head and shoulder angles were measured using side photography, and thoracic kyphosis angle was measured using a flexible ruler (r=0.093) before and after intervention. Paired t-test and analysis of covariance were used for data analysis at the significance level of P≤0.05. Results: The mean angles of forward head, forward shoulder and thoracic kyphosis decreased significantly after 8 weeks of NASM corrective exercise in the intervention group compared to the control group. Conclusion: Corrective trainers and therapists are advised to regularly use the NASM corrective exercise program proposed in this study for UCS patients.